Evaluation of fast track. - Combs, Shane; Chapman, Rose; Bushby, A. (Elsivier, 2007)
This paper is the second of two articles discussing the execution and evaluation of implementing a Fast Track program in a West Australian outer metropolitian hospital Emergency Department. The first paper in the series outlined the implementation process over a 12-month period. This current paper presents the findings of the 12 month-month evaluation utilising Statistical Process Charts. The object of this evaluation was to undertake analysis of data throughout the change process and demonstrate the effectiveness of implementing Fast Track into the Department. Following the implementation of FAst Track, the Department's "Did not wait" rate decreased over a 12 month period from 10% to 5.4%, without a detrimental impact on treatment times for the patients with serious illness and injuries. Furthermore, Fast Track resulted in patients with minor injuries or illnesses being seen, treated and discharged within 2 hours of presentation. Indeed the journey time decreased for all Emergency Department patients. As a result of FAst TRack, the Emergency Department waiting area is less congested and staff moral has increased. A further consequence of Fast Track is that nurses are providing more advanced clinical services to patients.